Characteristics and clinical manifestations of patients, including organ transplant patients, during the surge of JN.1: Insights from Saudi Arabia - Dalia A. Obeid; Ahmed A. Al-Qahtani; Reem S. Almaghrabi; Basma M. Alahideb; Layla A. Alharbi; Maha A. AlAbdulkareem; Talah M. Almadi; Madain S. Alsanea; Sahar I. Althawadi; Sara A. Altamimi; Fatimah S. Alhamlan (Elsevier, 2024)
Background: Amidst the persistent global health threat posed by the evolving SARS-CoV-2 virus throughout the four-year-long COVID-19 pandemic, the focus has now turned to the Omicron variant and its subvariant, JN.1, which has rapidly disseminated worldwide. This study reports on the characteristics and clinical manifestations of patients during the surge of the JN.1 variant in Saudi Arabia; it also investigates the evolution of SARS-CoV-2 variants in organ transplant patients and identifies patient risk factors. Methods: A total of 151 nasopharyngeal samples from patients with PCR-confirmed SARS-CoV-2 infection were collected between September 2023 and January 2024. Demographic and clinical data of the patients were obtained from electronic health records. All confirmed positive samples underwent sequencing using Ion GeneStudio and the Ion AmpliSeq™ SARS-CoV-2 panel. Results: During the surge of the JN.1 variant, the average age of the patients was 40 years, ranging from 3 to 93 years, and nearly 50% of the patients were male. Our investigation revealed that the J.N variant predominantly infected patients with comorbidities or organ transplant recipients (57.6%). Moreover, patients with comorbidities or organ transplants exhibited a higher number of mutations. In our organ transplant cohort, an increased total number of spike mutations was associated with a lower risk of developing severe disease (OR = 0.96, 95% CI: 0.93-0.98). Conclusions: Although JN.1 may not prove to be particularly harmful, it is crucial to recognize the persistent emergence of concerning variants, which create new pathways for the virus to evolve. The ongoing evolution of SARS-CoV-2 is evident in the continuous divergence of these variants from the original strain that marked the onset of the pandemic nearly four years ago.